AGAMA BAHAΓÇÖI PROBLEMATIKA PELAYANAN HAK-HAK SIPIL (Harmoni, 2014)
In the eyes of the law, the BahaΓÇÖi religion does not exist in this country, as it is not included in the six religions recognized in IndonesiaΓÇÖs constitution: Islam, Protestantism, Catholicism, Hinduism, Buddhism and Confucianism. As a result, it is considered an ΓÇ£unofficial ΓÇ£ or ΓÇ£unrecognized ΓÇ£ religion. In fact, in Article 29 Paragraph 2 of the 1945 Constitution and Article 1 of Law No. 1 / PNPS / 1965, the term ΓÇ£unofficialΓÇ¥ and ΓÇ£unrecognizedΓÇ¥ religion is not even used. The only term used are ΓÇ£followed and servicedΓÇ¥ religions. From this perspective, BahaΓÇÖi is not considered an independent religion, but a splinter group of other religions. This given rise to systemic losses, i.e the unfulfilled civil rights of BahaΓÇÖis, as part of Indonesian citizens who actually entitled to rights.
Keywords: BahaΓÇÖi; Civil Rights; Social Relations; Hak-hak sipil; Relasi Sosial